2022
DOI: 10.3389/fnagi.2021.801828
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Improves Spatial Memory, Anxiety-Like Behavior, and Motor Performance in Aged Male and Female Rats

Abstract: Aging is a progressive process leading to functional decline in many domains. Recent studies have shown that physical exercise (PE) has a positive influence on the progression of age-related functional decline, including motor and brain functions. Whole body vibration (WBV) is a form of passive stimulation by mechanical vibration platforms, which offers an alternative for PE interventions, especially for aged individuals. WBV has been demonstrated to mimic the beneficial effects of PE on the musculoskeletal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 77 publications
5
24
0
Order By: Relevance
“…In general, these findings are comparable with our previous study that reported that 10 min daily sessions of WBV in rats at the age of 18–20 months is able to alleviate anxiety-like behavior and improve motor activity in the open field test 64 . Interestingly, another study 47 showed that vibration with the frequency of 30 Hz, amplitude 4.5 mm and duration of 30 min per day has been demonstrated to alleviate anxiety-like behavior induced by restrain stress model.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, these findings are comparable with our previous study that reported that 10 min daily sessions of WBV in rats at the age of 18–20 months is able to alleviate anxiety-like behavior and improve motor activity in the open field test 64 . Interestingly, another study 47 showed that vibration with the frequency of 30 Hz, amplitude 4.5 mm and duration of 30 min per day has been demonstrated to alleviate anxiety-like behavior induced by restrain stress model.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the NLR test, the 20 min sessions of WBV group showed increased capability to distinguish the position of the relocated object in contrast to the 5 min sessions of WBV and pseudo treated animals, while the novel object discrimination index was not affected by vibration treatment. In addition, in previous study of our research group, the 10 min daily sessions of WBV was also able to improve this type of memory in aged rats 64 . Another study with young-adult mice with a similar methodical approach showed that vibration improved the performance in NOR test whereas the NLR test was not influenced 48 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Balance beam test was conducted twice on postoperative day 11 and 12 to analyze the motor coordination ( Oroszi et al, 2022b ). A 150 cm long and 2 cm wide wooden slat was positioned horizontally at 1 m above the floor, and on one end connected to the home cage of the rat, as target.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that vibratory training is an effective strategy to improve brain health and cognitive functions, as well as to counteract muscle atrophy and motor decline related to aging and/or a sedentary lifestyle [9,16]. In agreement, numerous studies over the last decades report among the main benefits of mechanical vibrations those affecting the musculoskeletal system, such as increased bone mass and muscle strength, as well as increased hormonal responses and improved cognitive abilities, anxious and depressive behavior, and neuromuscular adaptation [36,37]. However, cellular and molecular mechanisms through which vibratory training exerts its effects, influencing overall health, are largely unknown.…”
Section: Discussionmentioning
confidence: 83%